Tendencies of Reforming Legislative Regulation in the Field of Evidence in Civil Procedure of Ukraine - HRABOVSKA, Oksana O.; ZAKHAROVA, Olena S.; KARMAZA, Oleksandra O. (Journal of Advanced Research in Law and Economics, 2019)
The radical political changes that have taken place in recent years in connection with Ukraine's desire for integration into the European community have led to another judicial reform. As part of the legislative reform, a new version of the Code of Civil Procedure (CPC) was developed and adopted in 2017. The aim of this study is to identify, structure and analyze the fundamental changes that have occurred in the new version of the Code, and to trace outline trends in legislation of Ukraine of such concept as proof and reliability of evidence. The research substantiates the need to separate electronic evidence as an independent means of proof in civil justice, to analyze new innovations in Ukrainian law, and to show progressive vectors of change in civil law in Ukraine. This study may form the basis for further research into civil justice reform.